Rancang Bangun Prototipe Water Flow Meter Dan Level Air Pompa Dewatering Dengan Monitor Thingspeak Menggunakan Sumber Daya Tenaga Surya: Rancang Bangun Prototipe Water Flow Meter Dan Level Air Pompa Dewatering Dengan Monitor Thingspeak Menggunakan Sumber Daya Tenaga Surya (PETIR, 2023)
This design is based on dewatering pumps that often die and are not monitored, so that groundwater rises and penetrates into the basement area resulting in flooding. The cost of repairing a dewatering pump is quite expensive. The purpose of this research is so that water under the basement can be wasted and not cause flooding by utilizing solar power as an electrical power source. The monitor used is Thingspeak which gets the value of the Water Flow Meter that reads the rate of running water and height by installing a Magnetic Level Switch that sends commands to the Lamp. From the results of the testing of the design of the Thingspeak monitor and the reading of the Water Flow Meter, the hazard condition with a value of 1.83 Liters / minute with a live red indicator light. Testing safe conditions with a value of 4.74 Liters / minute with a green indicator light on. The efficiency of solar panels used with the specification of 50 Watt Peak with an efficiency value of 14.07%. The need for solar panel installation is 8,800 Watt Peak, so that 44 units of solar panels have a capacity of 200 Watts Peak. 12 units of battery needs with a capacity of 12V 200Ah. Inverter with a need of 6,000 Watts. Solar Charger Controler needs 400 A.